Tomato spotted wilt orthotospovirus (TSWV) is not transmitted by tomato seed - Dominguez, Guadalupe Rios; Salgado Siclán, Martha Lidya; Ortigoza, Carlos Aguilar; Aquíno Martínez, Jesus Gaudencio; Rámirez Davila, Jose Francisco (Revista Mexicana de Ciencias Agrícolas, 2019)
To date, more than 231 viruses capable of being transmitted by seed are reported externally or internally, this transmission is one of the most important factors in the epidemiological development of diseases of viral origin of early infection. The spotted wilt virus of the tomato spot wilt orthotospovirus (TSWV), Orthotospoviridae) affects more than 900 plant families including Solanaceae, its main transmission is by vector insects such as thrips, however, little is known of its possible transmission through of seed. The objective of this work was to determine the possible transmission of TSWV by seed of infected tomato plants using serological techniques and RT-PCR in its detection. Tomato fruits were collected from plants naturally infected with TSWV previously analyzed by Das-Elisa and positive for the virus from four regions of the State of Mexico. Subsequently, the seeds of the diseased fruits were extracted, one group had the detection of the virus by Das-Elisa in embryo and testa and the other group of seeds were grown in vitro culture for 15 days. Once the seedlings were obtained, RNA extraction and RT-PCR were carried out, using nucleocapsid-specific oligos. In vitro embryo, seed and seedling analyzes with Das-Elisa and RT-PCR (respectively) were found to be negative for TSWV in the treated samples. Apparently, there is no virus infection in in vitro embryo, testa and tomato seedlings.
Keywords: Solanum lycopersicum L.; in vitro; Das-Elisa; RT-PCR; seed; TSWV